Phenotypic Variability and Resource Allocation in Kashmir Sage (Phlomis cashmeriana Royle ex Benth.) in relation to Different Habitats and Altitudes: Phenotypic variability of Phlomis cashmeriana Royle ex Benth. in relation to different habitats - Roof Ul Qadir; Hanan Javid; Gowhar A. Shapoo; Bilal A. Wani; Junaid A. Magray; Irshad A. Nawchoo; Shabana Gulzar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Phlomis cashmeriana Royle ex Benth. commonly known as Kashmir sage is a rare and important medicinal plant growing in Kashmir Himalaya. The current study is the first of its kind, carried out to find the impingement on growth dynamics of the plant under study along various altitudinal inclines and habitats. Extensive field surveys were conducted during the years 2020-2021 to assess the distribution and phenotypic attributes of Phlomis cashmeriana. Three natural sites viz, Jawahar tunnel, Hillar naar, Daksum and one control population at KUBG were selected for the present work. Morphological characteristics of species were noticed to be varying extensively under different scopes of environment. Plants thriving at lower altitudes (KUBG) were found to be growing vigorously and taller. However, the opposite scenario was observed in plants growing at higher altitudes (Jawahar tunnel). KUBG and Daksum were reasonably found to be better habitats for the growth of Phlomis cashmeriana as revealed by principal component analysis (PCA). Majority of resources were attributed towards the growth of rhizomes followed by leaf, stem, and inflorescences respectively. Variation in reproductive success was also observed along different altitudes ranging from 63.94 % to 53.40 %. The total resource budget per plant also varied among different populations with a maximum in populations growing at low altitude, KUBG (23.73±6.63) and least in populations growing at high altitude J. tunnel (12.94±7.67). We hypothesize that a heterogeneous environment is the primary cause of phenotypic variability across different altitudes, however, the role of other environmental factors should also be taken into consideration.